YouTube as a Media in English Language Teaching (ELT) Context: Teaching Procedure Text - Abdul Khaliq Rasyid Nasution (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
Media is the one of tools that can help teacher in teaching and learning process in a class, especially in EFL classrooms. There are two kinds of media, such as visual and audio.In this article, the writer wants to use video as media in teaching-learning process, especially videos in YouTube. YouTube isn’t only have about fun videos, in YouTube can also use as learning media, in there we also can find so many education videos in every level, start from beginner, intermediate, and also for advanced level. In line with that, the writer wants to give video about how to make or do something or the other word we can say it “procedure”. The learning outcome is to make the students know about procedure text, especially in how to make and how to identify. Then, this article also wants to know YouTube is useful or not as learning media if we make it to support us in teaching and learning process.